The emergence and impact of ethylene scavengers techniques in delaying the ripening of fruits and vegetables - Mohd Affandy Aqilah Mariah; Joseph Merillyn Vonnie; Kana Husna Erna; Nasir Md Nur’Aqilah; Nurul Huda; Roswanira Abdul Wahab; Kobun Rovina (MDPI, 2022)
As the top grocery list priorities, the primary challenge when purchasing fruits and vegetables from supermarkets is obtaining fresh, minimally processed perishable goods. This source of diet is critical for obtaining vitamins, minerals, antioxidants, and fibres. However, the short shelf life caused by moisture content in rapid deterioration and decay caused by microbial growth, results in unappealing appearances. Fruits and vegetables undergo ripening and eventually the ageing process, in which the tissues of the plants degrade. Even after harvesting, numerous biological processes occur, generating a significant variation of ethylene production along with respiration rates between fruits and vegetables. Thus, the utilization of ethylene scavengers in food packaging or films has been revealed to be beneficial. The synergistic effects of these biomaterials have been demonstrated to reduce microorganisms and prolong the shelf life of greens due to antimicrobial activity, oxygen scavenging capacity, enzyme immobilization, texture enhancers, and nutraceuticals. The current review fills this void by discussing the most recent advances in research on ethylene scavengers and removal mechanisms of ethylene, including oxidation in fruit and vegetable packaging. The application and advantages of ethylene scavengers in packaging are then discussed with the addition of how the efficiency related to ethylene scavengers can be increased through atmospheric packaging tools. In this context, the article discusses characteristics, types of applications, and efficacy of ethylene control strategies for perishable commodities with the inclusion of future implications.